2021
DOI: 10.21203/rs.3.rs-455041/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prospective intra-individual blinded comparison of [18F]PSMA-1007 and [68Ga]Ga-PSMA-11 PET/CT imaging in patients with confirmed prostate cancer

Abstract: Introduction[18F]PSMA-1007 has potential advantages over [68Ga]Ga-PSMA-11, although limited prospective data evaluating diagnostic performance exist. The aims of this study are to describe the concordance of [18FPSMA-1007 and [68Ga]Ga-PSMA-11 for TNM with American Joint Committee on Cancer (AJCC) prognostic stage, and assess differences in tracer uptake.MethodsFifty men (mean age 71.8) were imaged with [68Ga]Ga-PSMA-11 and [18F]PSMA-1007 < 4 weeks apart. Images were independently reported according to TNM b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Nonrenal mode of excretion of 18 F-PSMA-1007 may help in detecting tumor lesions close to the ureter or urinary bladder, which can be masked by urinary tracer activity of 68 Ga-PSMA-11. This potential advantage may be more clinically relevant in detecting tumor recurrence 26 than in the setting of initial staging, as reported in a study by Pattison et al 18 comparing the 2 radiotracers with heterogeneous scan indications. They found discordant local T staging in 5/17 patients (higher T stage reported on 18 F-PSMA-1007 in all the 5 cases), discordant local recurrence in 3/33 patients (upstaging by 18 F-PSMA in all 3 cases), and discordant nodal staging in 3/14 patients with the major advantage being detection of lesions in proximity to the ureter and in detection of bladder wall invasion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nonrenal mode of excretion of 18 F-PSMA-1007 may help in detecting tumor lesions close to the ureter or urinary bladder, which can be masked by urinary tracer activity of 68 Ga-PSMA-11. This potential advantage may be more clinically relevant in detecting tumor recurrence 26 than in the setting of initial staging, as reported in a study by Pattison et al 18 comparing the 2 radiotracers with heterogeneous scan indications. They found discordant local T staging in 5/17 patients (higher T stage reported on 18 F-PSMA-1007 in all the 5 cases), discordant local recurrence in 3/33 patients (upstaging by 18 F-PSMA in all 3 cases), and discordant nodal staging in 3/14 patients with the major advantage being detection of lesions in proximity to the ureter and in detection of bladder wall invasion.…”
Section: Discussionmentioning
confidence: 97%
“…A recently published, retrospective, single-center study 17 comparing 68 Ga-PSMA-11 and 18 F-PSMA-1007 in 46 PCa patients found concordant mi(molecular imaging) TNM stages in 80.4% patients. Another prospective study 18 comparing the 2 tracers in 50 PCa patients found overall American Joint Committee on Cancer TNM prognostic stage concordance in 92% patients. A major drawback of both these studies was the heterogeneity in clinical indication for PSMA PET.…”
mentioning
confidence: 98%
“…14,15,17,18,[29][30][31][32][33][34][35][36] All studies were published between 2016 and 2021 (Table 1), 14,15,17,18,[29][30][31][32][33][34][35][36] and 58% (n = 7) of studies were published in 2021. 14,29,[32][33][34][35]37 Of the 12 studies, 7 were retrospective in design, 14,15,30,31,[33][34][35] with a larger sample size of 96 to 194 in 3 studies 14,15,34 than the other 5 prospective studies. 17,18,29,32,36 Among these 12 studies, 7 studies involved histopathological confirmation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Radiotracers used in PSMA PET scans are predominantly eliminated through the urinary system, which creates high background activity in the ureters, bladder, and urethra, complicating interpretation of imaging data. [9][10][11][12][13] In certain cases, intense radiotracer activity in these regions can be misinterpreted as pathological lesions, such as small pelvic lymph nodes or local PCa recurrence, particularly in anatomical structures close to the urinary tract. 9,11 One specific area of concern is the prostatic urethra, where retained urine may further complicate the interpretation of PSMA PET scans.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] In certain cases, intense radiotracer activity in these regions can be misinterpreted as pathological lesions, such as small pelvic lymph nodes or local PCa recurrence, particularly in anatomical structures close to the urinary tract. 9,11 One specific area of concern is the prostatic urethra, where retained urine may further complicate the interpretation of PSMA PET scans. Urine can be stagnated within the prostatic urethra for various reasons, including benign prostatic hyperplasia (BPH), prostatitis, postsurgical changes, or anatomical variations that can hinder the free flow of urine.…”
mentioning
confidence: 99%